KEBIJAKAN PERIZINAN PEMERINTAH KOTA PEKANBARU : STUDI KASUS IZIN TEMPAT USAHA REKLAME DI KOTA PEKANBARU DIJALAN PANGERAN HIDAYAT DAN KH.A DAHLAN TAHUN 2012-2013 - Jumeri, Anggya; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Now, Indonesia is doing development in every aspects lad to chane and improvement that may beable to improve public welfare. Realization of the development may be looked at the existence of its dwvwlopmwnt, like housing complex, bridges, roads, harbors and business or enterprises that uses machines with medium interference intensity like printing business in advertisement form. As constitutional state, there are some rules that bind society indevelopin their business. They are licensing business. The business licensing aims to prevent the danger of environment protect the certain objects and desire direct to certain activities such business licenses. The license of business place is one of the instrumnts that are very urgent in the government.In licensing business for advertising field, it is alleged that there are problems that are quite complex. Among them always happens conflict both internally and externally. The issue of licensing place of business is that the complexity of such a complexty of information flow, decision making and so forth. Because of that complexity, the issue of licensing maintenance of business premises causing conflict in the process. According to Robins (Organizational Behavior: 1979) says that the conflict is a process of interaction that occurs due to a discrepancy that occurs due to a discrepancy between the two opinions (point of view) that effects on the parties involved, the effect of positive and neative effects. It is the same as the opinion of Luthan ( Organizational Behaviour: 1981), he states that the conflict is a condition caused by the presence of opposing forces, these forces comes to the existence of human interests (resources). Conflict is closely linked to dissent, competition and differences desires or interests. There are serveral views on the impact of the conflict, including the view that a conflict on interest is a danger that some time may threaten the existence of a current and survival of an institutional or organization. These conflict need to be managed properly and required maximum efforts so that conflicts that occur can be directed to things that are positive.